Manajemen Program Adiwiyata Dalam Membentuk Karakter Peduli Lingkungan Di Smp Negeri 26 Gresik - Merry Puspitasari; Muslihun (Education Research Center, 2025)
Environmental problems in Indonesia show an increasing trend due to low public awareness in preserving nature. Education is one strategic approach to foster environmental awareness from an early age, one of which is through the Adiwiyata Program. This study aims to describe the management of the Adiwiyata Program and the strategy for developing environmentally conscious character at SMP Negeri 26 Gresik. The method used is qualitative with data collection techniques in the form of observation, interviews, and documentation. Data analysis was carried out through reduction, presentation, and drawing conclusions, while data validity was obtained through triangulation of sources and techniques. The results of the study indicate that the management of the Adiwiyata Program at SMP Negeri 26 Gresik was implemented effectively through structured planning, organizing involving the entire school community, implementing various routine and incidental environmental programs, and continuous evaluation. The strategy for developing environmentally conscious character was carried out through school policies, habituation, teacher role models, the use of environmentally friendly facilities and infrastructure, and active student participation. The Adiwiyata Program has been proven to contribute to shaping positive student behavior, such as disposing of waste in its place, sorting waste, caring for plants, and implementing environmentally friendly habits in daily life. Thus, the Adiwiyata Program plays a significant role in building environmentally conscious character in schools.